Effect of different compound fertilizer rates on Hevea brasiliensis grown on an Oxisol : nursery trial. - Mokhatar, Shafar Jefri; Daud, Noordin (2014)
One of the important commodity crops that contributed a lot to Malaysia’s economy was rubber tree or Hevea brasiliensis as this country was the biggest consumer of pure latex and the fifth in term of consumption of natural latex in the world. The precise usage of fertilizer is very important in rubber nursery establishment to ensure quality production of planting materials and optimization of fertilizing cost. This study will assess the current fertilizer suitability rate for latex timber clone and suggest fertilizer rate to be used in advanced planting materials nursery. The study was conducted using complete randomized design (CRD) with four replications. Four different rates of RISDA 1 compound fertilizer (10.7: 16.6: 9.5: 2.4) were used; T1 (0 g plant-1) act as control, T2 (50% or 18.75 g plant-1), T3 (100%: 37.5 g plant-1) and T4 (150%, 56.25 g plant-1). T3 (100%) were the rate recommended by the Malaysian Rubber Board (MRB). Soil used was a Typic Hapludox, Munchong Series. Data on growth such as height, girth and dry weight were taken. Tissue analysis was conducted at the end of the study. Results show that plants growth increased significantly with fertilizer application. Results show that K and Mg content were highest in T4 (150%) and significantly different from other treatments. Compared to established nutrient critical values for immature rubber, T4 met the nutrient sufficiency range for rubber, while current recommendation showed insufficient K and Mg. Visual observation also showed symptoms of nutrient deficiencies. From this study, based on biomass production and comparison of leaves nutrient with critical nutrient value, it can be concluded that the current recommended fertilizer rate were insufficient for the optimum growth.